Analysis of Factor Affecting Work Spirit in Employees PDAM Tirta Gemilang Magelang - Agil Nova Dwi; Didik Subiyanto; Tri Ratna Purnamarini (Equity: Jurnal Ekonomi, 2025)
The purpose of this study is to see how factors such as work motivation, work environment, and work stress affect the work spirit of employees of the Regional Drinking Water Company (PDAM) Tirta Gemilang Magelang which is one of the regionally owned business units, which is engaged in the processing and distribution of clean water for the general public workers. The quantitative methodology of this research relies on questionnaires that were randomly distributed to gather primary data. Using a Likert scale from 1 (strongly disagree) to 5 (strongly agree), researchers asked participants to rate their level of agreement with a series of statements. Using the slovin formula, a sample of 53 individuals was obtained from a population of 113 individuals in this research. Tests for validity and reliability, multiple linear regression analysis, tests for classical assumptions like normality, multicollinearity, and heteroscedasticity, and tests for hypotheses like t tests, f tests, and adjusted R2 are all part of the statistical toolbox. Next, SPSS 26 software was used to process the collected data. Work environment and motivation both significantly and positively impact work spirit, according to the study's findings. However, there is substantial evidence that stress at work lowers morale. Researchers interested in learning more about work spirit might use this study's results as a starting point. Furthermore, businesses may use the study's findings to influence policies that aim to boost employee morale and productivity.